2020
DOI: 10.1021/acsomega.0c01308
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Ultrafast Plasmonic Graphene Hot Electron Bolometric Photodetector

Abstract: We appraise a waveguide-integrated plasmonic graphene photodetector based on the hot carrier photo-bolometric effect, with performance characterized simultaneously by high responsivity, on the scale of hundreds of A/W, and high speed on the scale of 100's of GHz. Performance evaluation is based on a theory of bolometric effect originating from the band nonparabolicity of graphene. Results compare favorably with the state-of-the-art plasmonic bolometric photodetectors, predicting up to two orders of magnitude i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 85 publications
(383 reference statements)
1
43
0
Order By: Relevance
“…Thus, the compact devices can provide additional heat dissipation channel through the increases of T L but, simultaneously, reducing a PB effect [42]. It should be however noted that the efficiency of electron heating is independent of lattice temperature and depends only on the in-plane component of the electric field coupled to the graphene [34,61]. Recent studies showed that even rise the electron temperature T e to 1000's of K does not substantially move the lattice temperature T L away from the ambient temperature T 0 [65].…”
Section: Comparison With Other Graphene Based Plasmonic Photo-bolometersmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the compact devices can provide additional heat dissipation channel through the increases of T L but, simultaneously, reducing a PB effect [42]. It should be however noted that the efficiency of electron heating is independent of lattice temperature and depends only on the in-plane component of the electric field coupled to the graphene [34,61]. Recent studies showed that even rise the electron temperature T e to 1000's of K does not substantially move the lattice temperature T L away from the ambient temperature T 0 [65].…”
Section: Comparison With Other Graphene Based Plasmonic Photo-bolometersmentioning
confidence: 99%
“…Thus, in last few years a lot of effort focused on graphene photodetector. They can operate based on photovoltaic [20,33,42], photo-thermoelectric [43][44][45][46][47], or photo-bolometric [33,34,42,[48][49][50][51] effects. The choice of effect depends on a photodetector's configuration and specific applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this outstanding performance, the atomic thickness of graphene limits its interaction with guided optical modes, resulting in a relatively low current responsivity in the range of several mA/W [9]. To overcome this limitation, plasmon-enhanced graphene photodetectors have been proposed and demonstrated in [5], [7], [10]- [17], where a record-high Mohammed Alaloul is with the Department of Electrical and Computer Engineering, New York University Abu Dhabi, Abu Dhabi 129188, UAE (e-mail: malaloul@nyu.edu).…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting detectors, on the other hand, are faster (they can achieve few-picosecond response times [5]), broadband, and can achieve single-photon sensitivity [6], but they require a cryogenic environment to work, which makes them expensive and difficult to integrate with other systems. While nanoscale and low-dimensional hot-electron detectors are easier to integrate and can operate at a similar speed (on the scale of 100s of GHz [7]), this is still orders of magnitude slower than recently demonstrated detectors based on multiphoton or optical-field tunneling emission [8][9][10]. However, while the instantaneous current response from multiphoton and optical-field devices has demonstrated the capability to respond at petahertz-level frequencies, they also require strong fields (> 10 V nm −1 ) and are less sensitive than many alternative photodetection schemes.…”
Section: Introductionmentioning
confidence: 99%